Penggunaan Multimedia Interaktif dalam Meningkatkan Kreativitas dan Literasi Digital di Sekolah Dasar - Andika Adinanda Siswoyo; Muhammad Fahrudin Nasrullah; Muhammad Jamal Al Rosyid; Sevia Azzarah Riyanto; Rikza Fatimatuz Zahro; Rowienna Lintang Ramadhani Izdihara; Muhammad Danil Ainurrohman; Reza Alfian Firdaus (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
This research aims to determine the effectiveness of using interactive media in learning at SDN Modung 1, especially in increasing students' creativity and digital literacy. The research method involves three stages, namely preparation, implementation, and evaluation. The interactive media used include interactive PowerPoint (PPT), animated videos, and educational games. The results of the study showed that the use of interactive media significantly increased students' creativity in solving problems and generating new ideas, as well as digital literacy in operating technological devices and learning applications. In addition, students responded positively to interactive media, stating that learning became more interesting, interactive, and motivating. This study concludes that the application of interactive media in learning is effective in increasing students' creativity, digital literacy, and learning motivation, while preparing them to face the challenges of an increasingly digital future.